Insulin and Exendin-4 Reduced Mutated Huntingtin Accumulation in Neuronal Cells - Silvia Rea; David Della-Morte; David Della-Morte; David Della-Morte; Francesca Pacifici; Barbara Capuani; Donatella Pastore; Andrea Coppola; Roberto Arriga; Aikaterini Andreadi; Giulia Donadel; Nicola Di Daniele; et al. (Frontiers Media S.A., 2020)
Patients with diabetes mellitus (DM) are more prone to develop cognitive decline and neurodegenerative diseases. A pathological association between an autosomal dominant neurological disorder caused by brain accumulation in mutated huntingtin (mHTT), known as Huntington disease (HD), and DM, has been reported. By using a diabetic mouse model, we previously suggested a central role of the metabolic pathways of HTT, further suggesting the relevance of this protein in the pathology of DM. Furthermore, it has also been reported that intranasal insulin (Ins) administration improved cognitive function in patients with neurodegenerative disorders such as Alzheimer disease, and that exendin-4 (Ex-4) enhanced lifespan and ameliorated glucose homeostasis in a mouse model of HD. Although antioxidant properties have been proposed, the underlying molecular mechanisms are still missing. Therefore, the aim of the present study was to investigate the intracellular pathways leading to neuroprotective effect of Ins and Ex-4 hypoglycemic drugs by using an in vitro model of HD, developed by differentiated dopaminergic neurons treated with the pro-oxidant neurotoxic compound 6-hydroxydopamine (6-ohda). Our results showed that 6-ohda increased mHTT expression and reduced HTT phosphorylation at Ser421, a post-translational modification, which protects against mHTT accumulation. Pre-treatment with Ins or Ex-4 reverted the harmful effect induced by 6-ohda by activating AKT1 and SGK1 kinases, and by reducing the phosphatase PP2B. AKT1 and SGK1 are crucial nodes on the Ins activation pathway and powerful antioxidants, while PP2B dephosphorylates HTT contributing to mHTT neurotoxic effect. In conclusion, present results highlight that Ins and Ex-4 may counteract the neurotoxic effect induced by mHTT, opening novel pharmacological therapeutic strategies against neurodegenerative disorders, with the main focus on HD, still considered an orphan illness.